Pubic bone osteomyelitis and fistulas after radiation therapy of the pelvic region: patient-reported outcomes and urological management of a rare but serious complication - Walach, Margarete; Tavakoli, Andrej; Thater, Greta; Kriegmair, Maximilian; Michel, Maurice Stephan; Rassweiler-Seyfried, Marie-Claire (World journal of urology, 2024)
Purpose This study investigated late urinary adverse events (UAEs) in patients who underwent pelvic radiation therapy, with a focus on occurrence, diagnostic characteristics and the impact of subsequent extirpative surgery with the need of urinary diversion on quality of life. Methods A retrospective analysis of 20 patients after pelvic radiotherapy (2016-2022) was conducted. Data included demographics, perioperative details, oncological parameters, and patient-reported outcomes. Imaging (CT, MRI) was examined for early manifestations of late UAEs. Results In the study cohort, prostate cancer was the primary malignancy in 85% with a mean radiation dose of 84 Gray over 35 days. Time to diagnosis of late UAEs was 4.0 years post-radiation. Radiological assessment demonstrated a progressive increase in typical CT and MRI features of pubic bone osteomyelitis over time. Surgical interventions, mainly cystectomy, were required with variable outcomes in patient-reported post-surgery quality of life. Conclusion Diagnosing and managing late UAEs after pelvic radiation necessitate an understanding of their occurrence, diagnostic features and appropriate management strategies. Early imaging, particularly MRI, is crucial for timely diagnosis and treatment planning. Variable post-surgery quality of life underscores the importance of a multidisciplinary approach in managing late UAEs. The study contributes to understanding these complications and emphasizes their consideration in post-radiation follow-up care.